Professional occupation and the number of teeth retained among older adults aged 50 and above. (7th October 2014) - Zini, Avraham; Lewit, Chen; Vered, Yuval
Abstract : Objective: To examine the association between occupational characteristics and number of natural teeth retained among older adults aged 50 and above. Background: Despite the integral part of the professional occupation of a person's time, few studies have examined the effect of the occupational environment on one's oral health. Material and methods: Self‐administered questionnaires were randomly distributed among 280 participants, who had at least one professional occupation over a period of 10 years or more. Data from the questionnaire were collected concerning variables related to professional occupation and the self‐reported number of natural teeth retained. The data were analysed using a logistic regression analysis with stepwise‐backward selection. Results: Significant risk factors for the number of natural teeth being ≤25 were age ( p  < 0.001), years of education ( p  = 0.019) and a hospital/commercial environment of work ( p  = 0.021). The odds ratio for the number of natural teeth ≤25 increased with each year by 1.109, decreased with each additional year of education by 0.881, and was 2.693 folds higher for individuals working in a hospital/commercial environment compared to those in an office environment. Conclusions: These findings suggest the importance of operating community‐based oral health programmes for these occupational risk groups. The results from this study also implicate the need for further studies of this subject to find the underlying reasons for these occupational environmental risks.